Habilidades metafonológicas e conhecimento do nome das letras na alfabetização: estudo longitudinal com crianças do primeiro ano do ensino fundamental - Ramos, Adriana Príncipe dos Reis Albuquerque (2017)
There are evidences in the literature that thelearning of reading and writing is facilitated by phonological awareness and by the knowledge of the name of the letters. Current studies investigate which components of phonological awareness best predict reading and writing skills. The aim of this research was to analyze the relationship between the reading and writing of words with the variables of phonological awareness (measured by the knowledge of rhymes, syllabic segmentation and phonemic deletion) and knowledge of the name of the letters in children entering Primary School. For this, a brief longitudinal study was carried out accompanying the first year students of Elementary School during the school year. The study was composed of three data collection sessions, in which the students were evaluatedby a set of tasks of phonological awareness, knowledge of the alphabet, reading and writing of isolated words. The results showed a positive and significant correlation between letter knowledge, rhyme knowledge and phonemic deletion in the three collection moments with word reading. The syllabic segmentation obtained significant positive correlation only in the second collection. All components of phonological awareness, as well as letter knowledge, showed positive and significant correlations with word writing in three moments of the research. The results ofMultiple Regression tests(Stepwise)allowed the identification of knowledge of letter name and the knowledge of rhymes as predictors of reading and writing of words when the phonemic deletion did not obtain a measurable result. However, when the children started learning to read, the components of phonemic deletion and syllabic segmentation began to predict the reading of words with a high degree of significance, being the phonemic deletion also a predictor of word writing, accompanied by the knowledge of the names of the letters